2018
DOI: 10.1021/acsami.7b17454
|View full text |Cite
|
Sign up to set email alerts
|

Robust Anticancer Efficacy of a Biologically Synthesized Tumor Acidity-Responsive and Autophagy-Inducing Functional Beclin 1

Abstract: As a potent autophagy inducer, Beclin 1 is essential for the initiation of autophagic cell death, and triggering extensive autophagy by targeted delivery of Beclin 1 to tumors has enormous potential to inhibit tumor growth. Yet, the therapeutic application of Beclin 1 is hampered by its inability to internalize into cells and nonselective biodistribution in vivo. To tackle this challenge, we employed a novel Beclin 1 delivery manner by constructing a functional protein (Trx-pHLIP-Beclin 1, TpB) composed of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…Microtubule‐associated protein 1 light chain 3 (LC3) and p62/SQSTM1 are associated with autophagosomal membranes, which engulf cytoplasmic content for subsequent degradation (Schlafli et al, ). Beclin‐1 is a potent autophagy inducer and essential for initiation of autophagic cell death (He et al, ; Ding et al, ). It has been well accepted that autophagy plays an important role in the regulation of normal function of pancreatic β‐cells and insulin‐target tissues, such as skeletal muscle, liver, and adipose tissue (Barlow and Thomas, ).…”
Section: Introductionmentioning
confidence: 99%
“…Microtubule‐associated protein 1 light chain 3 (LC3) and p62/SQSTM1 are associated with autophagosomal membranes, which engulf cytoplasmic content for subsequent degradation (Schlafli et al, ). Beclin‐1 is a potent autophagy inducer and essential for initiation of autophagic cell death (He et al, ; Ding et al, ). It has been well accepted that autophagy plays an important role in the regulation of normal function of pancreatic β‐cells and insulin‐target tissues, such as skeletal muscle, liver, and adipose tissue (Barlow and Thomas, ).…”
Section: Introductionmentioning
confidence: 99%
“…It could be deduced that when 7pep-M-RAP is administered simultaneously with 7pep-M-PTX, or 7pep-M-RAP is administered after 7pep-M-PTX, cytotoxic PTX would firstly cause organelle damage, and then the autophagy induced by RAP might play a role in protecting MCF7 breast cancer cells from organelle damage caused by PTX. On the contrary, the pretreatment with 7pep-M-RAP on MCF-7 cells induced a large number of autophagy, resulting in excessive depletion of key intracellular processes and rapid accumulation of intracellular autophagic vesicles, whereas cells could not degrade the contents in time, leading to abnormal accumulation of autophagosomes and imbalance of cell functions46, 47. During autophagy development, the non-specific capture of cytoplasmic components led to irreversible damage to mitochondria or other organelles.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we found that JHC-4 at 100 μg/mL for 48 hrs could significantly induce the accumulation of cytoplasmic vacuoles ( Figure 1C and D), which were often observed in cells undergoing autophagy as abundant previous reports. 10,11 These data indicated that JHC-4 exhibited cytotoxic effect on gastric cancer cells and possibly induced autophagy.…”
Section: Jhc-4 Inhibited the Proliferation Of Human Gastric Cancer Bgmentioning
confidence: 84%
“…The accumulation of cytoplasmic vacuoles coincidently was observed after treatment, we thus suspected that autophagy might be the mechanism as abundant previously reported. 10,11 Autophagy is a lysosomal-dependent degradation pathway characterized by cytoplasmic vacuolization to maintain cell metabolism. Undoubtedly, it also plays a key role in cancer cell proliferation, chemosensitivity, immunoregulation, migration and so on.…”
Section: Introductionmentioning
confidence: 99%